Mindfulness Therapy for Autoimmune Diseases in Indonesia: Mechanisms, Applications, and Challenges - Sumah, Dene Fries; Lameky, Vernando Yanry; Parinussa, Nenny (Trends in Immunotherapy, 2025)
Mindfulness therapy, a psychological approach emphasizing awareness of the present experience without judgment, has gained attention as a potential intervention for improving the quality of life of patients with autoimmune diseases in Indonesia. With the increasing prevalence of autoimmune diseases and their associated physical and psychological symptoms, mindfulness therapy is highly relevant. This review explored the mechanisms of action, case studies, challenges, and recommendations for implementing mindfulness therapy in Indonesia. Mindfulness has been shown to modulate brain activity associated with emotional processing, reduce inflammation, improve pain management, enhance social relationships, and improve sleep quality. Case studies in Indonesia have demonstrated the effectiveness of mindfulness therapy in patients with rheumatoid arthritis and lupus, with participants reporting significant improvements in their physical and mental symptoms. However, challenges such as insufficient understanding among medical personnel, societal stigma, limited availability of programs, cultural factors, and lack of comprehensive research need to be addressed. Recommendations include enhanced education and training for medical personnel, public awareness initiatives, the development of culturally appropriate programs, improved accessibility, and further research on the effectiveness of mindfulness therapy in Indonesia. By addressing these challenges and implementing recommendations, mindfulness therapy can be effectively integrated into the Indonesian healthcare system to improve patient’s quality of life with autoimmune diseases.